Pigmentation of a Camouflage Dye and Investigation of Its Colour and Reflectance Properties - BALBASI*, MUZAFFER; ARDAHANLIOGLU, YAVUZ (Asian Journal of Chemistry, 2024)
Natural foliage and terrain reflect light both in the visible (380-700nm) and near infrared (700-900 nm) regions of the electromagneticspectrum. In this study, dyes consisting of several different pigmentcombinations are proposed intended to meet the camouflage needs fittingthe reflectance properties of local natural green foliage in both visibleand near infrared regions. Camouflage pigment green 179, functionalizedwith the appropriate infrared reflectance was mixed with varyingamounts of chromium oxide, iron oxide and carbozel violet pigmentsand the spectral reflectance of surfaces treated with this alkide based dyewas measured in the 320-1500 nm interval. Chromaticity and observedbrightness (Y) values were determined using the CIELAB 1976 (L* a* b*)colour definition systems. Field tests demonstrate that dyes thus obtained,meet camouflage standards in both the visible and near infrared regions.